PERBANDINGAN LAJU KOROSI PADA MATERIAL STEEL PLATE COLD COIL (SPCC) YANG DILAPISI CAT DENGAN RESIN YANG BERBEDA - Winda Yulliyanti; Devy Susanty; Wahyono Wahyono (Universitas Nusa Bangsa, 2016)
Comparison of Corrosion Rate on Steel Plate Cold Coil (Spcc) Material Coated With Different ResinIron corrosion is the most prominent problem because iron is widely used as a material, for example Steel Plate Cold Coil (SPCC) material or rolled steel plate that undergoes cooling process. SPCC materials are generally used for the manufacture of automobile engines, motor equipment, building construction, battery boxes, industrial machinery, and so on. The corrosion rate was determined by the salt blowing method. This method aims to calculate the corrosion rate of the material acting on an environment containing a salt solution such as NaCl. Corrosion rate testing was done on three types of paint (paint A, paint B, and C paint). Based on analysis and observation results, Coated Steel Plate Cold Coil material B coated has the smallest corrosion rate value because B paint has epoxy resin in the presence of aromatic aromatic compound ether, aromatic hydrocarbon and aliphatic alcohol.Keywords: Iron, Steel Plate Cold Coil (SPCC), corrosion, paintÂ ABSTRAKÂ Korosi pada besi merupakan masalah yang paling menonjol karena besi banyak digunakan secara luas sebagai material, contohnya material Steel Plate Cold Coil (SPCC) atau gulungan plat baja yang mengalami proses pendinginan. Material SPCC umumnya digunakan untuk pembuatan mesin mobil, peralatan motor, konstruksi bangunan, kotak baterai, mesin-mesin industri, dan sebagainya. Laju korosi ditentukan dengan metode sembur garam. Metode ini bertujuan untuk menghitung kecepatan korosi dari material yang bekerja pada lingkungan yang mengandung larutan garam seperti NaCl. Pengujian laju korosi dilakukan terhadap tiga jenis cat (cat A, cat B, dan cat C). Berdasarkan hasil analisis dan pengamatan, material Steel Plate Cold Coil yang dilapisi cat B memiliki nilai laju korosi terkecil karena cat B mempunyai resin epoxy dengan adanya senyawa aromatik eter, aromatik hidrokarbon dan alifatik alkohol.Kata Kunci: Besi, Steel Plate Cold Coil (SPCC), korosi, cat